Sampling the multivariate standard normal distribution under a weighted sum constraint - Frédéric Vrins (Risks, 2018)
Statistical modeling techniques-and factor models in particular-are extensively used in practice, especially in the insurance and finance industry, where many risks have to be accounted for. In risk management applications, it might be important to analyze the situation when fixing the value of a weighted sum of factors, for example to a given quantile. [...]
Keywords: 330; conditional distribution; conditional sampling; multi-factor models